How China's current carbon trading policy affects carbon price? An investigation of the Shanghai Emission Trading Scheme pilot. (20th April 2018) - Song, Yazhi; Liang, Dapeng; Liu, Tiansen; Song, Xiaoqiu
Abstract: To better establish a unified carbon market in China, this study evaluates the effect of current carbon trading policy and further investigates the relationship between such policy that is published during the second phase of Shanghai Environment and Energy Exchange (SEEE) and Shanghai Emission Allowance (SHEA) price. We aim to analyze whether these policies can improve the operation efficiency of current carbon market. By the Mean Reversion Test, Cox-Ingersoll-Ross (CIR) Model, and Event Study Method, we first analyze the potential price discovery function of SHEA products, thereby describing the transmission channel of current policy to SHEA price. Then we examine the effect of carbon policies published in different periods on their corresponding SHEA price. By the Auto-correlation Test and CIR simulation, we find that 3/4 of all auto-correlation values are less than 0 after Apr. 2017, and the minimum cumulative error is 31.3792 under the supply and demand channel. These findings imply that SHEA price has the discovery function at the middle and end of trading period, and the current policy affects SHEA price through its effect on the fundamentals of supply and demand. Further, more than 60% of all r-values (r-value that reflects the response of price to policy) are less than 1, which implies that the published policy will improves future SHEA price. Accordingly, we argue that SEEE belongs to a policy-oriented market, and the change of carbon price is closely related to emission allocation policies. In this case, China's government should further push forward the smooth operation of current carbon market by the aid of incentive policy in the coming period. Highlights: The operational state of Shanghai ETS pilot is evaluated. The effect of carbon trading policy on the price discovery function is examined. The transmission channel of carbon trading policy to carbon price is proposed. The period when carbon trading policy strongly affects carbon price is identified. The policy implications for China's unified carbon market are proposed.